Introduction to structural analysis - Podder, Debrabrata; Chatterjee, Santanu (Boca Raton, FL : CRC Press, 2022)
'This book cover principles of structural analysis without any requirement of prior knowledge of structures or equations. Starting from the basic principles of equilibrium of forces and moments, all other subsequent theories of structural analysis have been discussed logically. Divided into two major parts, this book discusses basics of mechanics and principles of degrees of freedom upon which the entire paradigm rests followed by analysis of determinate and indeterminate structures. Energy method of structural analysis is also included. Worked out examples are provided in each chapter to explain the concept and to solve real life structural analysis along with solutions manual'--
Includes bibliographical references (page 489-490) and index.
Keywords: Structural analysis (Engineering).